Correction: Orienting the causal relationship between imprecisely measured traits using GWAS summary data. - Gibran Hemani; Kate Tilling; George Davey Smith (PLoS Genetics, 2017)
[This corrects the article DOI: 10.1371/journal.pgen.1007081.].